From Huntington to Trump: Twenty-Five Years of the "Clash of Civilizations" - Haynes, Jeffrey (The review of faith & international affairs, 2019)
What is the explanatory value of the "clash of civilizations" paradigm, popularized by Samuel Huntington in the 1990s? How has Huntington's argument fared in the perceptions of scholars and policy makers, the two audiences on which he focused? In the three decades since Huntington first aired his controversial framework, inter-civilizational "clash" and "dialogue" have become mainstream issues in both international relations and in many countries' domestic concerns. The article focuses on the explanatory value of Huntington's "clash of civilizations" paradigm in relation to recent political successes of right-wing populists in the USA and Europe.